VILLAGES CARE FOR MIGRANT WORKER: ALTERNATIVE PREVENTION FOR UNDOCUMENTED MIGRANT WORKERS IN MADURA - Nuswardani, Nunuk; Yogahastama, Riesta; Yogahasama3, Riesta (International Journal of Psychosocial Rehabilitation, 2020)
The absence of migrant workers’ safe migration information and legal procedure knowledge is the main reason to why they become undocumented workers, leading to deportation as consequence. Most of migrant workers chose the unofficial pathways to work due to the deficiency in safe migration information, unverified migrating villagers’ data by the village authority, and the document management by the drops. Therefore, the roles of local inhabitants and the local authorities are important to cut the chain of migration problems off. The development of migrant worker villages as an alternative prevention for non-procedural Indonesian Migrant Workers (PMI henceforth) is thus required. This employs empirical law approach. The current research aims to investigate the roles of the migrant worker villages in preventing the non-procedural PMI. The research was undertaken in Pamekasan and Sampang Districts. The Law of Protection of Indonesian Migrant Workers (PPMI henceforth) mandates all villages to take apart in offering the protection to the migrant workers. The programs of Productive Migrant Villages (Desa Migran Produktif (Desmigratif, henceforth)) offer four main services: providing migration service center, running productive business for PMI and their families, creating Desmigratif workshop, and facilitating the formation and development of financial institutions. The interview done in Karang Penang village (Sampang) and Pesanggar village (Pamekasan) indicated that those villages are the pilot projects where Desmigratif in each district operates. In addition, Desmigratif offered infrastructure development in villages at 2017. Running productive business has become the major concern in Desmigratif programs. Desmigratif also shares safe migration information with the migrant workers, works hand in hand with employment agencies. Desmigratif in Pamekasan and Sampang have been efforts to undocumented PMI prevention.